The Kudus Traditional House as a Potential Tropical Building Design for Climate Action - Anisa Anisa (Sustainability Science and Resources, 2022)
One of the Sustainable Development Goals is Climate Action, meaning taking immediate actions to combat climate change and its impacts. This study evaluates the potentials of Indonesian traditional houses in helping mitigating climate change in the tropics. As a case study, the author analyses the designs of Kudus traditional house built primarily in the old city of Kudus, the province of Central Java, Indonesia. The study employs qualitative research, making use of primary data from field observations and interviews. Field observations were carried out to identify design elements of the traditional houses, while interviews were undertaken to obtain data and information on how the designs deal with climate problems. The results show that the Kudus traditional houses are designed in such a way that minimizes the need for air conditioning and energy uses given the hot tropical climate. The designs include the following: (1) building masses are built with an open yard in the middle of the masses’ configuration; (2) building masses are extended from north to south direction; (3) optimization of openings, for lighting and ventilation, on the walls and the roof of the building; (4) The use of a sloping roof with a wide eaves. Although the climate has changed, the traditional Kudus house is still comfortable to use for activities. This proves that the traditional Kudus house is still relevant in responding to the local climate.